Kinematically exact elastoplastic analysis of steelo rods with compact cross sections. - Sousa, Yuri Teixeira e (2017)
In this work, we present the formulation and implementation of two elastoplastic constitutive equations for kinematically exact thin-walled rod models. The first uses the fact that first order strains due to cross sectional shear stresses and warping are considered to formulate a small strains three-dimensional elastoplastic constitutive model. Given the kinematical hypothesis of non-deformability of the cross section in the projection of its plane, we may also assume that plastic deformations may occur due only to the cross sectional normal stresses, thereby allowing us to formulate a second, simple one-dimensional framework. Our approach adopts a standard additive decomposition of the strains together with a linear elastic relation for the elastic part of the deformation. Both ideal plasticity and plasticity with (linear) isotropic hardening are considered. The models have a computational implementation within a finite element thin-walled rod model and, following the kinematics adopted, we implement this equation on models with consideration of the warping of the cross sections, having 7 degrees of freedom. The formulation and implementation presented is validated by the analysis of problems known in the literature and comparison of the results. We believe that simple elastoplastic models combined with robust thin-walled rod finite element may be a useful tool for the analysis of thin-walled rod structures, such as, e.g., steel structures.